Asymptomatic bilateral chemodectomas: a masquerader of simple neck masses - Naveen Chandrashekhar Pawar; Shivani Sharma; Navkiran Kaur; Amarjit Kaur (International Journal of Medical Research and Review, 2017)
Patients presenting with asymptomatic neck masses to surgical OPD can have many differentials, ranging from the simplest reactive lymph nodes to aggressive malignant masses. Bilateral neck masses in a patient can be due to infective lymph nodes, salivary gland pathology, solid - cystic lesions of the neck and malignancies. Based on the anatomical site of the lesion, clinical examination still remains the first step in characterising the lesion into solid, cystic, pulsatile, non pulsatile, response to cough impulse and so on. Imaging is always a mandatory next step for the confirmation of diagnosis and to know about the morphology of the lesion with finer details. USG, CT and MRI are indispensable tools in assessing neck masses with equivocal findings on clinical examination and particularly in asymptomatic individuals where there is lack of history and thus diagnosis becomes a challenging task. One such entity is bilateral Chemodectomas where imaging plays a pivotal role in the diagnosis. We report a case of bilateral neck masses in an asymptomatic female patient which on imaging was diagnosed as a case of bilateral carotid body tumours and referred to higher centre for further management.